PENGARUH PUPUK KANDANG KAMBING DAN SAPI TERHADAP PERTUMBUHAN Azolla microphylla - Arif, Faiz Al; Susanto, Herry; Pujisiswanto, Hidayat (JURNAL AGROTROPIKA, 2021)
Azolla microphyllais a type of small fern that lives in the waters. One of the benefits of this plant is as an organic fertilizer in lowland rice cultivation. Considering its population in nature is decreasing while the use is increasing, it is necessary to conduct a research how to increase the growth and population of A. microphylla. The research was conducted at the Greenhouse and Weed Science Laboratory of the Faculty of Agriculture, University of Lampung from March to April 2020. The study used a completely randomized design (CRD) with four replications and six treatments so that there were 24 experimental units. As growing media, soil and 10.5 liters of water are filled in a tray measuring 30 cm x 35 cm. The treatments were KO = without manure, K1 = goat manure 42 g, K2 = goat manure 31,5 g plus cattle manure 10,5 g, K3 = goat manure 21 g plus cattle manure 21 g, K4 = goat manure 10,5 g plus cattle manure 31,5 g, and K5 cattle manure 42 g that added in 10,5 liters of water. Homogeneity of data was tested using the Bartlett test, the additivity was tested with the Tukey test. The mean was tested with the least significant difference (LSD) at 5% level. The results showed that the use of goat and cattle manures and the its mixture increased the growth and development of Azolla microphylla. The mixture of goat manure 21 g and cattle manure 21 g / 10.5 liters water is the best treatment for population growth of Azolla microphylla. Â Keywords: Azolla microphylla, growth, manure, mixture, population